TRUDNOŚCI (SAMO)OCENY W NAUCZANIU JĘZYKA POLSKIEGO JAKO OBCEGO W BIZNESIE - Komorowska, Ewa (Neofilolog, 2019)
Teaching business Polish to foreign businessmen in Poland has its specificity: lessons often take place in learners’ offices on a one-to-one basis or in very small groups. Learners are usually very demanding and autonomous. They want to have control over their language learning process but are unwilling to take any tests. Therefore, process of evaluation has to be organized in a less conventional manner. The article reflects on the needs of such learners and describes the most effective ways which, according to its author, measure their skills: formative assessment and task-based assessment.